2014
DOI: 10.1063/1.4868109
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ferroelectricity of nonstoichiometric (Na0.5Bi0.5)TiO3

Abstract: The ferroelectric domain structure of pure Na 1/2 Bi 1/2 TiO 3 (NBT) and 1 at.% Mn-doped NBT (Mn-NBT) crystals was investigated by piezoresponse force microscopy. The correlation length of the polar regions was found to increase upon Mn substitution. High resolution transmission electron microscopy revealed that the coherency of the lattice across the domain boundaries between polar regions was also enhanced. Selected area electron diffraction showed that Mn favored coexisting 1/2 (ooo) and 1/2 (ooe) oxygen oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Such is the case of some BNT-based ceramics even in the unpoled state [11,79,80]. For BNT and BNT-based and other lead-free ferroelectric ceramics, this strategy has been widely used [70,81,82,83,84,85,86,87]. …”
Section: X-ray Diffraction and Scatteringmentioning
confidence: 99%
See 3 more Smart Citations
“…Such is the case of some BNT-based ceramics even in the unpoled state [11,79,80]. For BNT and BNT-based and other lead-free ferroelectric ceramics, this strategy has been widely used [70,81,82,83,84,85,86,87]. …”
Section: X-ray Diffraction and Scatteringmentioning
confidence: 99%
“…The 1D experiment is more sensitive to surface effects at low Bragg angles, which explains why one might do one or the other depending on if surface effects are the focus of the experiment. In literature, one can find informative studies that carry on Rietveld structural refinement of single conventional or synchrotron X-ray diffraction patterns with flat specimens and coupled θ–2θ scans, of ferroelectrics after the application of electric field [70,73,78,81,82,83,84,85,86,87,88,89]. …”
Section: X-ray Diffraction and Scatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it has been reported that non-stoichiometric compositions deviated from (Na 0.5 Bi 0.5 )TiO 3 , e.g. Bi-deficient/Na-excess compositions of (Na 0.5+x Bi 0.5Àx )TiO 3+x , resulted in dramatically deteriorated ferroelectric properties and were unable to be poled to induce piezoelectric functions [8]. To date, the origins producing the property deviation remain unclear due to lack of microstructure information of the piezoelectric NBT-BT films.…”
Section: Introductionmentioning
confidence: 98%